Client satisfaction and quality of curative services for sick children in Nepal: further analysis of the 2015 Nepal Health Facility Survey: DHS further analysis reports No. 114. - Acharya,Kiran (2018)
ABSTRACT: This study assessed the quality of care at health facilities in providing sick child care, using data from the 2015 Nepal Health Facility Survey. The measures of quality of care were divided into structure (infrastructure of the facility and availability of commodities), process (provider's performance), and outcomes (client's overall satisfaction with services). Associations between client satisfaction and structural and process attributes were analyzed using multiple regressions. The average readiness score of health facilities to provide sick child services was 54.9, with some variation among different types of facilities, ecological regions, and provinces. The score was similar between public and private facilities. In examining process factors, we found that the large majority of children (86%) diagnosed with pneumonia received correct treatment, while less than half (44%) of those diagnosed with diarrhea received correct treatment. Among the structural factors, such as frequency of services in a week, 24-hour availability of health workers, availability of an ORT corner and emergency transport, toilets for clients, etc.-though important aspects of quality of care-we found none significantly associated with client satisfaction. Process attributes, however, such as waiting time less than 30 minutes and receiving information from providers about the child's illness, were significantly associated with higher client satisfaction. KEY WORDS: quality of care, service readiness, client satisfaction, sick child curative care, Nepal